Spectroscopic measurements of atmospheric N2O at Syowa Station, Antarctica: Preliminary results - Makino, Yukio; Muramatsu, Hisafumi; Kawaguchi, Sadao; Yamanouchi, Takashi; Tanaka, Masayuki; Ogawa, Toshihiro (1985)
P(論文) Spectroscopic measurement of atmospheric trace constituents at Syowa Station, Antarctica (69°00'S, 39°35'E) was started on 24 March 1983. Preliminary results of this measurement are presented. Total atmospheric nitrous oxide (N_2O) deduced from the transmittance of solar radiation at 2576(cm)^<-1> (3.88 μm) indicated a seasonal variation with a maximum in spring. The deduced mixing ratios of N_2O were smaller than the value of 300 ppbv measured by a gaschromatographic technique. The method of analysis was also examined in terms of the atmospheric models to be used and it was shown that a multi-layer model should be applied to the case of solar zenith angle larger than 85°. departmental bulletin paper